2010
DOI: 10.1136/jme.2010.037440
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons' opinions and practice of informed consent in Nigeria

Abstract: Background Informed consent is perhaps more relevant to surgical specialties than to other clinical disciplines. Fundamental to this concept is the provision of relevant information for the patient to make an informed choice about a surgical intervention. The opinions of surgeons in Nigeria about informed consent in their practice were surveyed. Methods A cross-sectional survey of surgeons in Nigeria was undertaken in 2004/5 using self-administered semistructured questionnaires. Results There were 102 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 16 publications
2
34
1
1
Order By: Relevance
“…There are aspects of our findings that resonate with previous studies exploring doctors’ perspectives of informed consent for surgical procedures in other countries . Our doctors noted that working in time‐pressured environments affects the quality and amount of information they impart to patients, consistent with findings from previous focus‐group and questionnaire‐based studies …”
Section: Discussionsupporting
confidence: 89%
“…There are aspects of our findings that resonate with previous studies exploring doctors’ perspectives of informed consent for surgical procedures in other countries . Our doctors noted that working in time‐pressured environments affects the quality and amount of information they impart to patients, consistent with findings from previous focus‐group and questionnaire‐based studies …”
Section: Discussionsupporting
confidence: 89%
“…This suggests a gap between expectations and practice and could mean that although the level of ethical practices may be encouraging, doctors need to do more to satisfy the expectations of this patient population. In contrast to a recent survey that showed that surgeons in South West Nigeria considered informed consent to be “alien to African psyche,”5 the findings in this study show that urban women in the South East Nigeria value information and respect for their opinions. The differences in the two studies may be due to the study populations (doctors versus pregnant women), but it may also suggest that doctors may need to begin to modify their attitude towards medical ethics in developing societies, like Nigeria.…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, medical ethics is evolving rather slowly in Nigeria, and even physicians are unsure of the direction it should take 5. For instance, approximately 73% of surgeons surveyed in a recent study in Nigeria agreed that informed consent “was alien to the African psyche.”5 There remains substantial doubt about whether western-style medical ethics practices are sustainable in Africa, given the cultural and socioeconomic differences between the two societies 2,4–7…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report the results of a survey among Nigerian surgeons on communication between them and their patients. In a previous publication, we reported the opinions of the surgeons and their practice of informed consent from data obtained from the same survey [5]. …”
Section: Introductionmentioning
confidence: 99%